2017
DOI: 10.1158/0008-5472.can-16-2204
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Induction Supporting Breast Cancer Cell Survival Is Enabled by Oxidative Stress–Induced DPP3–KEAP1 Interaction

Abstract: NRF2 is a transcription factor serving as a master regulator of the expression of many genes involved in cellular responses to oxidative and other stresses. In the absence of stress, NRF2 is constantly synthesized but maintained at low levels as it is targeted by KEAP1 for ubiquitination and proteasome-mediated degradation. NRF2 binds KEAP1 mainly through a conserved “ETGE” motif that has also been found in several other proteins, such as DPP3, which has been shown to bind KEAP1 and enhance NRF2 function upon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 37 publications
(50 reference statements)
0
130
0
1
Order By: Relevance
“…Nrf2 pathway activation by DPP3 has been clearly shown to be independent of DPP3 enzymatic activity. (30) In this respect, we showed almost complete lack of enzymatic function in vitro in our Dpp3 KO mouse using a standard synthetic substrate, but we did not systematically look for DPP3 substrate in vivo. A series of compounds have been proposed to play this role, mainly through in vitro studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nrf2 pathway activation by DPP3 has been clearly shown to be independent of DPP3 enzymatic activity. (30) In this respect, we showed almost complete lack of enzymatic function in vitro in our Dpp3 KO mouse using a standard synthetic substrate, but we did not systematically look for DPP3 substrate in vivo. A series of compounds have been proposed to play this role, mainly through in vitro studies.…”
Section: Discussionmentioning
confidence: 88%
“…(24) It has been purified from several murine and human biological sources and has been proposed to act in the terminal stages of protein turnover, in the framework of several pathophysiological processes through the hydrolysis of bioactive peptides, (24)(25)(26)(27) in metabolic, cardiovascular, and neoplastic diseases. (25,26,(28)(29)(30) For the first time, here we demonstrate DPP3 protein expression in the bone tissue and uncover its role in bone pathophysiology, taking advantage of our newly generated Dpp3 knockout (KO) mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…The list of all the proteins that interact with NRF2 in the human interactome is available online at http://sbi.imim.es/data/nrf2/. 352 formation underlining colon (Gonzalez-Donquiles et al, 2017) and breast (Lu et al, 2017) tumors.…”
Section: B Positioning Nuclear Factor (Erythroid-derived 2)-like 2 Amentioning
confidence: 99%
“…Recently, it was shown that dipeptidyl-peptidase 3, which bears an ETGE motif, may compete with NRF2 for binding to KEAP1 (Hast et al, 2013). Overexpression of dipeptidyl-peptidase 3, possibly induced by chronic alteration of the redox status, correlates with increased expression of ARE genes and poor prognosis, particularly in estrogen receptor-positive breast cancer (Lu et al, 2017).…”
Section: Systems Medicine Approach To Nrf2 In Chronic Diseasesmentioning
confidence: 99%
“…(12,19, 20)]. In addition to stress-related activation, a number of proteins [e.g., p21 (21), p62, PALB2, IKKB, DPP3 (22) and iASPP (23)] can competitively bind to Keap1 and inhibit Nrf2 ubiquitination. Inactivation of Keap1 allows de novo synthesized Nrf2 to translocate to the nucleus and either transduce or suppress target genes [Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%